2017
DOI: 10.1373/clinchem.2016.269969
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inflammatory and Cardiovascular Biomarkers for Prediction of 90-Day All-Cause Mortality after Acute Ischemic Stroke—Results from the Linz Stroke Unit Study

Abstract: In this large cohort of patients with acute ischemic stroke, IL-6 and NT-proBNP at admission were strong and independent prognostic markers for 90-day all-cause mortality, and provided complementary prognostic information to the routinely used stroke severity score NIHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 25 publications
3
35
1
1
Order By: Relevance
“…In line with previous reports suggesting a multimarker approach to improve outcome prediction in AIS patients [27], our data indicate that calprotectin either alone or even better when combined with CRP and NLR could improve the overall prediction of 3-month mortality in AIS, suggesting that an elevated in ammatory state may contribute to the mortality in AIS patients. Though, the predictive capacity of this multimarker approach in our cohort and the robust results on K-fold internal cross-validation, it will need further external validation in other cohorts of AIS patients.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous reports suggesting a multimarker approach to improve outcome prediction in AIS patients [27], our data indicate that calprotectin either alone or even better when combined with CRP and NLR could improve the overall prediction of 3-month mortality in AIS, suggesting that an elevated in ammatory state may contribute to the mortality in AIS patients. Though, the predictive capacity of this multimarker approach in our cohort and the robust results on K-fold internal cross-validation, it will need further external validation in other cohorts of AIS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, sST2 levels were found to independently correlate with 90-day mortality and hemorrhagic transformation after AIS [9]. However, the predictive value of sST2 for all-cause mortality 90 days after ischemic stroke showed no statistical significance after multivariate adjustment [10]. Our data supported and further reported the independent predictive value of sST2 for long-term prognosis after TIA/ischemic stroke (composite adverse events and a combination of major disability and death at 1 year).…”
Section: Discussionsupporting
confidence: 74%
“…Elevated sST2 is also associated with increased risk of hemorrhagic transformation, 90-day poor functional outcomes, and higher mortality after acute ischemic stroke (AIS) [8,9]. However, results have been mixed, with another study reporting that sST2 offered no prognostic value for 90-day all-cause mortality after AIS in multivariate analysis [10]. The present study aimed to investigate the predictive value of serum sST2 for long-term prognostic outcomes in a cohort of patients with TIA/ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated sST2 has also been shown to be related to worse outcome and higher mortality after AIS [17]. However, the conclusions from another study in a large cohort of AIS patients revealed that serum sST2 may not be a strong and independent prognostic marker for AIS mortality [18]. To date, the relationship between circulating levels of sST2, stroke severity, and post-ischemic inflammation has not been well elucidated.…”
Section: Introductionmentioning
confidence: 99%